Development Of Android-Based Applications With An Inquiry Approach On Solubility Material And Solubility Products As A Source Of Independent Learning For High School Students - Jakub Saddam akbar; Djakariah; Aisyiah Restutiningsih Putri Utami; Kurniahtunnisa4; Ayu Febrianti Akbar (Universitas Islam Kuantan Singingi, 2024)
This study aims to develop an Android-based application that uses an inquiry approach on solubility material and solubility products, and assesses its feasibility as an alternative source of independent learning for high school students. The approach used is the development research method, by choosing a development design using the ADDIE model. The result of this study is in the form of an Android-based application. The evaluation of the results of this development is based on the assessment of validators who show very good categories, with ideality reaching 86% according to the assessment of media experts, and 84.75% according to the assessment of material experts. Student responses to Android-based applications with an inquiry approach to solubility material and solubility results obtained a percentage of 93.22%. Based on the expert assessment and student responses, it can be concluded that the Android-based application that has been developed is worthy of being used as an independent learning resource for high school students.